2014
DOI: 10.1055/s-0034-1372510
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Absence of Intraoperative Neural Response Telemetry in Children using Cochlear Implants

Abstract: Introduction Currently the cochlear implant allows access to sounds in individuals with profound hearing loss. The objective methods used to verify the integrity of the cochlear device and the electrophysiologic response of users have noted these improvements. Objective To establish whether the evoked compound action potential of the auditory nerve can appear after electrical stimulation when it is absent intraoperatively. Methods The clinical records of children implanted with the Nucleus Freedom (Cochlear Lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…There is a dearth of literature where the surgeons have reported and shared their experiences with the intraoperative cochlear implant device failure attributable to hardware or software errors. Moura et al 3 in their case series followed up children with absent intraoperative NRT and concluded that 45% of such children responded positively to continued electrical stimulation after an average of 4.9 months, which they explained by hypothesizing that synaptic activity can be altered by continuous electric stimuli by providing sustained neurotrophic support to the auditory nerve. Thus, the absence of intraoperative NRT in the series was not due to hardware or software malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of literature where the surgeons have reported and shared their experiences with the intraoperative cochlear implant device failure attributable to hardware or software errors. Moura et al 3 in their case series followed up children with absent intraoperative NRT and concluded that 45% of such children responded positively to continued electrical stimulation after an average of 4.9 months, which they explained by hypothesizing that synaptic activity can be altered by continuous electric stimuli by providing sustained neurotrophic support to the auditory nerve. Thus, the absence of intraoperative NRT in the series was not due to hardware or software malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…2 Intraoperative NRT, in conjunction with electrode impedance data, can help indicate the integrity of the implanted electrodes and the electrode/auditory nerve interface, confirming that the implant functions correctly intraoperatively. 8 There have been differences of opinion regarding the usefulness of the intraoperative ECAP threshold in setting the map of the speech processor. 9,10 There is significant variation in neural response from patient to patient, and it indicates differences in stimulated neural population due to myelination, the presence of a dendritic population, and axonal integrity in the residual auditory neural population, according to Tanamati et al 11 It was also found that all the intraoperative ECAP thresholds were the highest values recorded.…”
Section: Discussionmentioning
confidence: 99%